Comprehensive evaluation of functional components, biological activities, and minerals of yam species (Dioscorea polystachya and D. alata) from China. (1st October 2022) - Wang, Putao; Shan, Nan; Ali, Asjad; Sun, Jingyu; Luo, Sha; Xiao, Yao; Wang, Shenglin; Hu, Rui; Huang, Yingjin; Zhou, Qinghong
Abstract: Yam ( Dioscorea spp.) is a multi-species and multi-purpose tuber crop. In this study, the contents of functional components, biological activities, and mineral elements were evaluated in the yam tubers of D. polystachya and D. alata cultivated widely varieties in China. Significant differences in allantoin contents were observed between interspecific and intraspecific yam varieties, and allantoin contents in the four varieties of D. polystachya were significantly higher than those in the D. alata group; however, no significant difference was observed for dioscin levels in all accessions. Furthermore, the phenol and flavonoid contents of D. alata were higher than those of D. polystachya . Protein profiles obtained using nano-liquid chromatography-tandem mass spectrometry (nanoLC-MS) revealed that the levels of proteins related to allantoin, total phenols, and total flavonoids also changed. In addition, both D. polystachya and D. alata tubers contained highly essential minerals, such as high potassium and magnesium, and low heavy metal contents within the specified pollutant content range. This study provides a foundation for the functional food development of Chinese yams and a reference for breeding high-quality yam varieties. Highlights: Allantoin content in D. polystachya is significantly higher than that in D. alata. D. alata has higher total phenols and flavonoids than D. polystachya. Both D. polystachya and D. alata have high K element and low heavy metal.